2021
DOI: 10.1108/neje-07-2020-0028
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the motivation of social entrepreneurs in creating successful social enterprises in East Africa

Abstract: PurposeThis paper aims to investigate the motivations of social entrepreneurs in East Africa to create a social enterprise and their identified links to successful social entrepreneurship in East Africa.Design/methodology/approachThe authors employed a qualitative method by performing thematic analysis on a set of interviews on social entrepreneurs from East Africa who are Ashoka fellows.FindingsThe findings suggest that intense personal experiences linked to past-life events as well as a high achievement orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 97 publications
3
21
0
1
Order By: Relevance
“…We thus distinguish pursuing financial success from retaining financial security for a person's financial motive and suggest that social entrepreneurs, while not particularly motivated by financial returns, desire financial security at an individual level (Au et al, 2021;Boluk and Mottiar, 2014). Indeed, some social entrepreneurs consider a social enterprise an option for self-employment (Wanyoike and Maseno, 2021) while many others operate the social enterprise because they want minimal compensation/support to maintain their families (Ruskin et al, 2016). Such individuals may work full-time to attain their social mission and may lack alternative income opportunities.…”
Section: Perceived Financial Securitymentioning
confidence: 99%
“…We thus distinguish pursuing financial success from retaining financial security for a person's financial motive and suggest that social entrepreneurs, while not particularly motivated by financial returns, desire financial security at an individual level (Au et al, 2021;Boluk and Mottiar, 2014). Indeed, some social entrepreneurs consider a social enterprise an option for self-employment (Wanyoike and Maseno, 2021) while many others operate the social enterprise because they want minimal compensation/support to maintain their families (Ruskin et al, 2016). Such individuals may work full-time to attain their social mission and may lack alternative income opportunities.…”
Section: Perceived Financial Securitymentioning
confidence: 99%
“…From this perspective, training institutions see these challenges as an interesting area of opportunity to address various factors involved in the failure or survival of social projects. Wanyoike and Maseno (2021) conducted research in East Africa where they found that the personal experiences of entrepreneurs have a determinant impact on the development of JARHE 14,3 social entrepreneurship proposals, which also, according to Ahmed et al (2020), can be influenced by the family support that entrepreneurs have. Emotionally speaking, Darmanto and Pujiarti (2020) warn that emotional intelligence can affect several areas such as selfefficacy, intention and support for the environment, among others, when carrying out social entrepreneurship projects.…”
Section: Social Innovation and Entrepreneurshipmentioning
confidence: 99%
“…In addition, although there are several studies on the personality of the entrepreneur, most of the existing research in the area has focused essentially on the institutional level (Nascimento & Salazar, 2020), so some authors suggest a focus on the individual (Fridhi, 2021;Saebi, Foss, & Linder, 2018). This seems particularly important when talking about motivations for entrepreneurship, more specifically with understanding the role of action (Sadílek, Kročil, & Müller, 2022;Wanyoike & Maseno, 2021;Yamini, Soloveva, & Xiaobao, 2022).…”
Section: Introductionmentioning
confidence: 99%